2021
DOI: 10.1007/s00259-021-05343-x
|View full text |Cite
|
Sign up to set email alerts
|

Value of [68Ga]Ga-FAPI-04 imaging in the diagnosis of renal fibrosis

Abstract: Renal brosis is a pathological state in the progression of chronic kidney disease. Early detection and treatment are vital to prolong the survival of patients. Renal puncture examination represents the gold standard examination method for renal brosis, but it has several limitations. This study aims to evaluate the diagnostic performance of a novel PET radiotracer, [ 68 Ga]Ga-broblast activation protein inhibitor (FAPI)-04, which speci cally images broblast activation protein (FAP) expression for renal brosis.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 39 publications
2
62
1
Order By: Relevance
“…Fibrosis markers are needed in the evaluation of schistosomiasis: in this context, an interesting PET radiopharmaceutical may be represented by 68 Ga-labeled fibroblast activation protein inhibitor ( 68 Ga-FAPI), a recent tracer that targets the fibroblast activation protein [ 91 ]; this radiopharmaceutical has been used to assess the degree of fibrosis in organs such as liver and kidneys [ 91 , 92 ] and potentially it may be useful for the assessment of fibrosis induced by schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis markers are needed in the evaluation of schistosomiasis: in this context, an interesting PET radiopharmaceutical may be represented by 68 Ga-labeled fibroblast activation protein inhibitor ( 68 Ga-FAPI), a recent tracer that targets the fibroblast activation protein [ 91 ]; this radiopharmaceutical has been used to assess the degree of fibrosis in organs such as liver and kidneys [ 91 , 92 ] and potentially it may be useful for the assessment of fibrosis induced by schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…A 65-year-old woman with rectal cancer showed enhanced 68 Ga-FAPI uptake in her sacroiliac and costal joints, suggesting that she had sacroiliac arthritis and spondylitis, while 18 F-FDG PET/CT found no abnormal lesions on the bone ( 66 ). MIP images of a 49-year-old male patient showed increased FAPI intake in the middle abdomen, which was followed by a pathological diagnosis of benign enteric inflammatory myofibrolastoma ( 67 ). Scholars have also found that FAPI-guided radiation therapy may reduce selective lymph node irradiation, thereby avoiding tumor recurrence and improving overall survival.…”
Section: Organs Of the Abdominal Cavitymentioning
confidence: 99%
“…The SUV max of the patients with mild, moderate, and severe fibrosis were 3.92 ± 1.50, 5.98 ± 1.6 and 7.67 ± 2.23, respectively. Thus, in comparison with renopuncture examinations, 68 Ga-FAPI-04 PET/CT showed bilateral kidneys more quickly and sensitively, which can, in turn, help assess disease progression, diagnosis, and treatment planning ( 67 ).…”
Section: Organs Of the Abdominal Cavitymentioning
confidence: 99%
“…We purchased the precursor FAPI-04 from MCE (MedChemExpress, USA), with a purity of 98% and a quality of 872.91. The 68 Ga-FAPI labeling was carried out according to the method described previously [9]. The radiochemical purity of 68 Ga-FAPI exceeded 95%.…”
Section: Ga-fapi Pet/ctmentioning
confidence: 99%